Life-Threatening Dermatoses and Emergencies in Dermatology - Revuz, Jean; Roujeau, Jean-Claude; Kerdel, Francisco; Valeyrie-Allanore, Laurence (Springer Berlin Heidelberg : Imprint: Springer, 2009)
Since extensive dermatoses can be life threatening, it is important to recognize and treat skin emergencies rapidly. This book covers all cutaneous emergencies and life threatening dermatoses, as well as true and false emergencies in the dermatologic office. It provides treatment advice for the management of major life threatening dermatoses, such as severe infections, severe drug eruptions and bullous diseases. In addition, it describes the manifestations in acutely ill patients in the ICU, as well as severe cutaneous manifestations occurring during pregnancy, after sun exposure, in cold weather, as a result of extreme poverty, and in other situations. With diagnostic clues, reader-friendly charts and clinical photographs, this clinical guide will not only benefit the hospital-based dermatologist, but will also be a helpful guide for non-dermatologists, such as ER and ICU physicians.